Water Supply and Waterbornes Diseases in the Population of ZaKpota Commune (Benin, West Africa) - ODOULAMI, Léocadie; DANSOU, Brice Saturnin; Kpoha, Nadège (My University, 2018)
The population of the common Za-kpota is subjected to several difficulties bound at the access to the drinking water. This survey aims to identify and to analyze the problems of provision in drinking water and the risks on the human health in the township of Za-kpota. The data on the sources of provision in drinking water in the locality, the hydraulic infrastructures and the state of health of the populations of 2000 to 2012 have been collected then completed by information gotten by selected 198 households while taking into account the provision difficulties in water of consumption in the households. The analysis of the results gotten watch that 43 % of the investigation households consume the water of well, 47 % the water of cistern, 6 % the water of boring, 3% the water of the Soneb and 1% the water of marsh. However, the physic-chemical and bacteriological analyses of 11 samples of water of well and boring revealed that the physic-chemical and bacteriological parameters are superior to the norms admitted by Benin. The consumption of these waters exposes the health of the populations to the water illnesses as the astroenteritis, the diarrheas, the affections dermatologic,... to fight against these water illnesses, the measures of sensitization of the populations for the adoption of the hygienic behaviors in the township of Za-kpota are to consider.
Keywords: Bénin; Za-kpota commune; water supplied; water pollution; waterborne disease